Fenomena Flexing Culture Di Media Sosial Mahasiswa Pendidikan Agama Islam : Perspektif Krisis Pendidikan Islam - Jannah, Raudhatul; Ajahari, Ajahari; Lutfi, Saiful (Jayapangus Press, 2024)
Islamic Religious Education students as future religious educators need to realize the importance of limiting the content shared on social media to maintain integrity and ethics in accordance with Islamic values. This is to keep activities on social media reasonable and not contradict their role as role models in society. This study aims to describe the motives of flexing culture of Islamic Education students at IAIN Palangka Raya on social media and find out how the phenomenon of flexing culture on social media of Islamic Education students according to the perspective of the Islamic Education crisis. The method used in this research is a qualitative approach using descriptive data. This research uses data collection techniques in the form of interviews and documentation, which are analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the main motive of Islamic Religious Education students class 2020 class A semester 8 IAIN Palangka Raya behind this flexing culture is from internal encouragement, the phenomenon of flexing culture among Islamic Education students has two different sides in the context of the Islamic Education crisis. On the one hand, sharing academic achievements and positive activities can motivate and build a good self-image. However, if done with the intention to boast, this can reduce the quality of Islamic education and obscure religious values. There needs to be a higher awareness among Islamic Education students regarding the wise use of social media in order to avoid the potential for irritation, feelings of inferiority, and the development of negative perceptions among the community.